Effects of Whole Body Vibration and Resistance Training on Bone Mineral Density and Anthropometry in Obese Postmenopausal Women - Moushira Erfan Zaki (Journal of Osteoporosis, 2014)
Objective. The aim of this study was to evaluate the impact of two exercise programs, whole body vibration and resistance training on bone mineral density (BMD) and anthropometry in obese postmenopausal women. Material and Methods. Eighty Egyptian obese postmenopausal women were enrolled in this study; their age ranged from 50 to 68 years. Their body mass index ranged (30–36 kg/m2). The exercise prescription consisted of whole body vibration (WBV) and resistance training. Bone mineral density (BMD) and anthropometrical parameters were measured at the beginning and at the end of the study. Changes from baseline to eight months in BMD and anthropometric parameters were investigated. Results. BMD at the greater trochanter, at ward's triangle, and at lumbar spine were significantly higher after physical training, using both WBV and resistive training. Moreover, both exercise programs were effective in BMI and waist to the hip ratio. Simple and multiple regression analyses showed significant associations between physical activity duration and BMD at all sites. The highest values of R2 were found for the models incorporating WBV plus BMI. Conclusion. The study suggests that both types of exercise modalities had a similar positive effect on BMD at all sites in obese postmenopausal women. Significant association was noted between physical activity and anthropometric variables and BMD measures at all sites.